Drug resistance of tuberculosis patients at the Makassar city community lung health center hospital: case study - Teresia Talantan Kondolele; Dian Mirza Togubu; Musfirah Achmad (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Drug-resistant tuberculosis (TB-RO) is still a health problem because of its rapid transmission with an increasing number of cases. Objective: This study aims to discover in-depth patient knowledge about tuberculosis and the family's role in treating drug-resistant tuberculosis patients. Methods: This research uses a qualitative case study approach with nine informants. The selection of informants was determined using a purposive sampling technique. Data collection was obtained through interviews and observations. Data analysis was carried out qualitatively. Result: The research shows that informants' knowledge about drug-resistant tuberculosis depends on their educational history. In contrast, informants with low educational backgrounds only know the term tuberculosis but do not know the causes and dangers of drug-resistant tuberculosis. Another thing that was found was that the family also played a role in the patient's treatment by providing support and encouragement for the informant during the treatment period. Conclusion: This research concludes that the informant's knowledge about tuberculosis plays an essential role in the occurrence of drug-resistant tuberculosis. The role of the family does not contribute to the occurrence of drug-resistant tuberculosis in the informant. It can be concluded that the earlier the age of menarche increases the risk of uterine myoma later in life. In contrast, slower menarche may be associated with a reduced risk of myomas. Other factors such as genetic, environmental, and lifestyle factors also influence the incidence of uterine myomas, but menarche age is one of the significant hormonal indicators of risk.